Labor Optimization and Capital Support for Increasing The Turnover of Cassava Rengginang Home Industries in Rubaru District, Sumenep Regency - Suto; Iriani Ismail (Economics and Business Journal (ECBIS), 2026)
This study aims to analyze the effect of labor optimization and capital support on the turnover of cassava rengginang home industries in Rubaru District, Sumenep Regency. The study employed a quantitative approach using a time series method with secondary data collected from 2012–2024. The variables analyzed consisted of capital and labor as independent variables and turnover as the dependent variable. Data analysis was conducted using multiple linear regression supported by classical assumption tests. The findings indicate that capital has a positive and significant effect on turnover, with a regression coefficient of 4.68 and a probability value of 0.0000. Meanwhile, labor shows a significant negative effect on turnover, with a coefficient value of -3.68 and a probability value of 0.0460. Simultaneously, capital and labor contribute significantly to turnover improvement, with an R-squared value of 0.912, indicating that 91.2% of turnover variation can be explained by both variables. The results emphasize the importance of effective labor management, workforce productivity improvement, and adequate capital support in enhancing the performance and sustainability of cassava rengginang home industries in Rubaru District.